Comparison of Effectiveness in Flexor Tendon Hand Repairs between WALANT Technique and Conventional Method - Srisai, Chinnawat; Jianmongkol, Surut (Journal of Southeast Asian Orthopaedics, 2022)
Objective: To compare the effectiveness in flexor tendon hand repairs between wide-awake local anesthesia no tourniquet (WALANT) technique and conventional method. Methods: The study design of this study was randomized controlled trials (RCTs) in 92 patients with flexor tendon repairs. Patients were divided into 2 groups: 46 were operated under the WALANT technique and 46 controls were operated under the conventional method. All study subjects have hand tendons surgery at the Department of Orthopedics, Roi Et Hospital from June 1, 2018 to December 31, 2019. The pain score, total blood loss, duration time of surgery, and patient satisfaction were recorded. The statistics analyses were used descriptive and Mann-Whitney U test. Results: The comparison of effectiveness in flexor tendon hand repairs between WALANT technique and the conventional method were found no signiﬁcant differences between two groups in terms of pain score preoperative (p=0.941), pain score intraoperative (p=0.774), total blood loss (p=0.291), operative time (p=0.078), and overall satisfaction (p=0.274). Conclusion: This study revealed that the effectiveness in flexor tendon hand repairs between WALANT technique and conventional method in terms of pain score, total blood loss, duration time of surgery and patient satisfaction is not signiﬁcantly different.